Reflection on nursing care for women in abortive situations: Challenges and perspectives (Research, Society and Development, 2024)
Abortion, a phenomenon involving the interruption of pregnancy, can occur spontaneously or be induced and is surrounded by cultural, political, and ethical controversies. In Brazil, abortion is illegal except in specific cases, which leads many women to seek unsafe methods, exposing themselves to significant risks. The objective of this article is to present a study on women’s perceptions of the nursing care received during and after abortion, considering the fundamental role of nursing professionals in providing humanized and holistic care. Using a narrative literature review, existing knowledge on the topic was analyzed, highlighting socioeconomic, cultural, and demographic factors influencing abortion. It was found that nursing care should go beyond physical care, encompassing emotional and social aspects, promoting ethical and empathetic support. It is concluded that strengthening humanized health practices is essential to improve the quality of care provided to women undergoing abortion, as well as to reduce the physical and emotional impacts of this experience.